The Solanum torvum Transcription Factor StoWRKY6 Mediates Resistance against Verticillium Wilt - Yu Zhang; Lei Shen; Liangjun Li; Xu Yang (Agronomy, 2022)
WRKY is a transcription factor family that has attracted much attention in recent studies of plant disease resistance, but there are few reports in the study of eggplant resistance to Verticillium wilt. Here, we retrieved an up-regulated WRKY transcription factor, StoWRKY6, from the transcriptome sequencing data of Solanum torvum response to Verticillium dahliae infection. Phylogenetic analyses revealed the highest homology species of StoWRKY6 in the WRKY family is Solanum melongena. Based on the quantitative real-time PCR analysis, StoWRKY6 was highly expressed in the roots but barely expressed in the leaves. Transient expressions of StoWRKY6 in Nicotiana benthamiana showed a nuclear localization. A virus-mediated gene silencing experiment indicated that the silencing of StoWRKY6 reduced the resistance to Verticillium wilt in Solanum torvum. To further verify the immune response function, we introduced StoWRKY6 into Nicotiana benthamiana using transient transformation technology and found obvious spots under UV light. In summary, these results showed that StoWRKY6 played an important role in the resistance to Verticillium wilt of Solanum torvum, which may function mainly by inducing an immune response. Our study provided strong evidence for the mechanism of eggplant resistance to Verticillium wilt and laid a foundation for the potential molecular breeding of eggplant disease resistance.